Balancing technical and user objectives in the redesign of a peruvian cookstove. (2017) - Thacker, Kendall S.; Barger, K. McCall; Mattson, Christopher A.
Abstract: Over the past decade a large amount of research has been dedicated in academic literature to improving the technical capabilities of improved cookstoves; primarily the performance efficiency and reduction of emissions. Unfortunately, as published literature has highlighted, the trade-offs that result from placing such a concentrated emphasis on these technical objectives is that improved cookstoves lack the same level of usability as the traditional cookstoves. Thus, users often return to using their traditional stoves and the potential impact of the improved cookstoves is never fully realized. In order for improved cookstoves to have greater impact, there must be better balance between the two competing design objectives of technical capabilities and usability. This paper explores the challenges and benefits associated with achieving the appropriate balance, and demonstrates its application through the modification of a traditional cookstove used in the Tambogrande region of Peru. This modification includes an inexpensive set of pot skirts that integrate directly with the traditional stove. These pot skirts allow for varying sizes and number of pots, and the use of traditional fuels. Laboratory testing, using the Water Boiling Test (WBT), identified the skirts' technical improvements: 41.7% increased thermal efficiency, 32.7% decreased fuel consumption, 28.8% decreased time to boil. Field testing was performed to determine the pot skirts acceptance and compatibility with the traditional cookstoves, with over 75% of the participants recognizing some type of benefit. Although the technical improvements of these pot skirts are less than other cookstoves on the market, the higher levels of usability are likely to lead to a more positive end-user reaction, which could potentially lead to higher rates of adoption and impact. Though these results are primarily focused on the application of improved cookstoves, the need for more balance between technical and user objectives is applicable to nearly all products being designed for the developing world.